Sexuality and Religious Ethics: Analysis in a Multicultural University Context - Navarro-Prado, Silvia; Sánchez-Ojeda, María Angustías; Fernández-Aparicio, Ángel; Vázquez-Sánchez, María Ángeles; Plaza del Pino, Fernando Jesús; Alemany-Arrebola, Inmaculada (IOAP-MDPI, 2023)
Sexuality is still perceived by some cultures as a taboo subject. Although there is now a more open attitude towards sexuality, the maintenance of virginity is one of the most concerning issues in some religions. The aim of this research is to investigate the sexual behavior of university students and analyze how culture and religion influence the beliefs and maintenance of virginity in women and men. A mixed methodology was used, involving 355 students in the quantitative design and 18 informants for the qualitative study who took part in two focus groups. The results indicate that religion and the degree of religious practice are predictor variables for the decision to have penetrative sex, with Muslim women and men giving more importance to the maintenance of a woman’s virginity. However, this hymen-centric view does not prevent other sexual practices, such as oral and/or anal sex, among young people who wish to maintain their virginity until marriage. Religious ethics continue to influence the sexual behavior of young people today. Therefore, nursing education must address these issues to improve the affective sexual health of the population.
Keywords: Sexo; Sexual abstinence; Sexuality; Young adult; Culture; Religious ethics